THE PRESENT SITUATION REGARDING INTERRELIGIOUS DIALOGUE AND COMMUNICATION IN JAPAN - Sottocornola, Franco (2000)
The aim of this article is to give a general description of the present -L situation regarding interTeIigious dialogue in Japan from a Christian-Catholic perspective. To do this we will need, first, to have a general idea Of the present religious situation in Japan, and to consider some very peculiar aspect of it, which may bear on the question of interreligious dialogue.
Keywords: Communication; Interreligious Dialogue